Green information systems adoption: a theoretical framework based on design science research - Machado, Petruska de Araújo (2018)
The increasing scarcity of natural resources, the accelerating pollution of the environment, and the looming threat of global climate change have attracted the interest of IS scholars. The environmental damages have affected the economy and caused social injustice due to the consequences of global warming. Some of the main drivers of global warming are from anthropogenic activities associated with the waste generation. Given these needs, green information systems (Green IS) would be an alternative for reducing the environmental impacts and promoting sustainable development in organizations. Nevertheless, some uncertainties towards of the Green IS adoption are associated with various obstacles, unknown challenges, and the complex understanding of the relation between technology, organization, and environment. One of the great challenges of environmental action lies in knowing what to do, limiting the ability to develop plans which are able to address such issues. The prior literature does not explore deeply “how” people act surrounding of the complex issues into the Green IS adoption process. Yet, there is a lack of appropriated theory to understand how individuals make the decision to adopt Green IS initiatives. This current research aims to outline a framework for the green information systems adoption. It analyzes the phenomenon using Design System Theory as theoretical lenses and multi-method approach. To build the framework, it has followed the steps of the design science as well as the design-science research guidelines. The analysis aimed identifying the general principles of the Green IS adoption in a organizational level through deductive and inductive processes. First, deductive process has been performed by scientometric analysis and systematic literature review. Second, inductive process has conducted semistructured interviews performed with individuals of the three universities involved in the sustainability projects. The analysis was based on thematic analysis, using cognitive mapping techniques performed by Atlas.ti software. The results provide um framework that helps practitioners to know what must be done when the organizations decide to undertake green information systems. The framework represents a differential for suggesting a schema non-linear to understand the phenomenon. The empirical findings of this research reveal that there are four three topics need to be emphasized in respect to green information systems adoption such as human’s behavior related to the motivational forces, system development and design, and goals and strategies for sustainability. Theoretically, the application of the framework can be tested in any organization using green information systems for monitoring environmental performance. It also suggests methodological procedures showing how it can be measured for future validation.